Peran Financial Distress Sebagai Variabel Mediasi antara Good Corporate Governance dan Kinerja Keuangan, Terhadap Manajemen Laba Pada Bank Umum Syariah Periode 2013-2019 - Syadzwina Ramadhana Fitriza; Rika Lidyah; Tariza Putri Ramayanti; Titin Hartini; Mismiwati Mismiwati (Esensi: Jurnal Bisnis dan Manajemen, 2021)
This study aims to determine the effect of good corporate governance and financial performance on earnings management with financial distress as an intervening variable in Islamic Commercial Banks in Indonesia. This type of research is descriptive research with quantitative approach. The results showed that good corporate governance has no effect on earnings management. Financial performance and financial distress have a negative and significant effect on earnings management. Good corporate governance has a negative effect on financial distress. Financial performance has no effect on financial distress. Then, based on the result of path analysis through the causal step method, financial distress mediates the effect of good corporate governance on earnings management, while financial distress does not mediate the effect of financial performance on earnings management.